Introduction - Hartvig, Gabriella; Maczelka, Csaba (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Overview of the issue with reference to the English and Irish Women Writers of the Long Eighteenth Century, Pécs, 24-25 Nov 2023 conference (https://womenwritersup.wordpress.com/).